Involvement of the Heat Shock Protein HtpG of Salmonella Typhimurium in Infection and Proliferation in Hosts - Dong, Tao; Wang, Weiwei; Xia, Minhao; Liang, Shujie; Hu, Guangzhong; Ye, Hui; Cao, Qingyun; Dong, Zemin; Zhang, Changming; Feng, Dingyuan; Zuo, Jianjun (Frontiers in Cellular and Infection Microbiology, 2021)
Salmonella Typhimurium is a common pathogen infecting the gastrointestinal tract of humans and animals, causing host gastroenteritis and typhoid fever. Heat shock protein (HtpG) as a molecular chaperone involves in the various cellular processes of bacteria, especially under environmental stress. However, the potential association of HtpG with S. Typhimurium infection remains unknown. In this study, we clarified that HtpG could also play a role as an effector in S. Typhimurium infection. RNA-seq indicated that the flagellar assembly pathway, infection pathway, and chemotaxis pathway genes of S. Typhimurium were down-regulated after the mutation of HtpG, which resulted in compromises of S. Typhimurium motility, biofilm formation, adhesion, invasion, and inflammation-inducing ability. In addition, HtpG recombinant protein was capable of promoting the proliferation of S. Typhimurium in host cells and the resultant inflammation. Collectively, our results illustrated an important role of HtpG in S. Typhimurium infection.